Transformações espaciais no centro de Fortaleza: estudo crítico das perspectivas de renovação urbana - Fernandes, Francisco Ricardo Cavalcanti (2004)
This research analyses the urban an environmental perspectives for downtown Fortaleza in the context of the globalization flows and in the context of insufficiency of the structure an management models based on the Master Plans' juridical instruments, once the market relationships dominate in the contemporary urban space production process. It starts on a survey about the lines of direction and physical interventions proposed on the physicalterritorial plans for the city and the functional and flows homogenization that emerge with the space metropolization and with the decentralization of central activities caused by the vertical urban expansion. The research approaches to the "downtown issue" starting from the following questions: lost of the symbolic reference condition that come out with the emergency of new centralities and the intra-urban movement of residential, government and entertainment equipments; immobility of the physical structure along the metropolitan expansion process, which is characterized by the economical dependency of near towns on Fortaleza; structures degradation cycle, effect of low investment that produces the condition of "periphery's downtown"; Urban structure inertia and public managers and planners narrowness of understanding about the emergency of new spatial needs imposed by the dynamics of the global economy and the fact that recent government project for spatial adaptation of strategic city areas do not include downtown as a touristic site. The analysis look into four urban renewal projects which were presented in the "National Competition of Ideas for Embellishment and Valorization for Downtown Fortaleza and Park of the City", organized by N.G.O. Ação Novo Centro - which is attached to PLANEFOR - Strategic Plan for the Metropolitan Region of Fortaleza - in 1999. This competition had for objective bringing together global propositions for downtown Fortaleza that intended it's spatial, landscaping, functional end environmental restoration, life quality improvement and new activities attraction to make it more competitive, re-establish heterogeneous flows, revert the functional specialization condition and produce a new image for that area. The project's analysis intends to confront different downtown conceptions, evaluate their viability in view of contemporary economic dynamic and to discuss it's ideological contents. At last, the research think over the perspectives for downtown starting from the articulation among local government, firms and society, with emphasis to the importance of the technical action over the urban form - through the urban and architectural design - as a condition to induce the renewal, and alerting to the necessity of assuming the design as an important instrument in the environment organization process.